Happily ever afters - Bryant, Elise (Elise M.) (2021)
Sixteen-year-old Tessa Johnson has never felt like the protagonist in her own life. She's rarely seen herself reflected in the pages of the romance novels she loves. The only place she's a true leading lady is in her own writing--in the swoony love stories she shares only with Caroline, her best friend and #1 devoted reader. When Tessa is accepted into the creative writing program of a prestigious art school, she's excited to finally let her stories shine. But when she goes to her first workshop, the words are just...gone. Fortunately, Caroline has a solution: Tessa just needs to find some inspiration in a real-life love story of her own. And she's ready with a list of romance novel-inspired steps to a happily ever after. Nico, the brooding artist who looks like he walked out of one of Tessa's stories, is cast as the perfect Prince Charming. But as Tessa checks each item off Caroline's list, she gets further and further away from herself. She risks losing everything she cares about--including the surprising bond she develops with sweet Sam, who lives across the street. She's well on her way to having her own real-life love story, but is it the one she wants, after all?
Ages 14-19.
Keywords: African American teenage girls -- Juvenile fiction; Teenage girls -- Juvenile fiction; Authorship -- Technique -- Juvenile fiction; Man-woman relationships -- Juvenile fiction; Teenagers -- Juvenile fiction; Creative writing -- Juvenile fiction; Anxiety -- Juvenile fiction; Teenage girls; Authorship -- Technique; Man-woman relationships; Women authors -- Fiction; African Americans -- Fiction; Love -- Fiction; Interpersonal relations -- Fiction; Art schools -- Fiction; Schools -- Fiction; Inspiration -- Fiction; Creative ability -- Fiction; Young adult fiction; Women authors -- Fiction; African Americans -- Fiction; Love -- Fiction; Interpersonal relations -- Fiction; Art schools -- Fiction; Schools -- Fiction; Inspiration -- Fiction; Creative ability -- Fiction; Young adult fiction; Romance fiction